Considering an Appreciative Approachto International Extension Evaluation - Alexa J. Lamm; Kevan W. Lamm (Journal of International Agricultural and Extension Education, 2018)
Programmatic evaluation has become a common practice in international extension education. Evaluation has primarily been used to report the outputs, outcomes and impacts of extension efforts. Sometimes an evaluation is done for formative reasons, to make programmatic improvements, and most often for summative reasons, as a justification for further funding. Depending upon the evaluator (or evaluative approach) the evaluation will include stakeholder input and focus on collecting data the stakeholder will ultimately use. Some have even gone so far as engaging in developmental evaluation which allows for ambiguity and changes in direction throughout the duration of an extension program. Despite the many ways the discipline evaluates, almost every evaluation takes a problem-solving approach where areas for improvement are identified. The purpose of this manuscript was to reflect upon past evaluation practice within the international extension literature and discuss the role appreciative evaluation can play as evaluation continues to inform international extension efforts
Keywords: extension; evaluation; appreciative inquiry; utilization-focused evaluation